ANALISIS FREKUENSI DATA SEISMIK HASIL MIGRASI FINITE DIFFERENCE - Jamaluddin .; Johanes Gedo Sea; Yusuf Surachman Djajadihardja; Muhammad Altin Massinai; Sabrianto Aswad; Maria . (Jurnal Geosaintek, 2019)
Finite difference migration is one of the migration algorithms that uses the principle of downward continuation and upcoming waves which are solved numerically with finite difference. This migration in ProMAX software has various algorithms depending on the numerical solution used. From each finite difference migration algorithm this shows a significant difference in the frequency produced. Migration with the explicit finite difference algorithm shows better frequency results than the Implicit Finite Difference algorithm.